Nanoparticulate BDNF as a potential antidepressant via neuroendocrine mechanisms in experimental model of depression - Nur Amirah Diyana, Razlan; Marina, Kapitonova; Saiful Bahri, Talip; Gabriele Ruth Anisah, Froemming; Tin, Moe Nwe (Sarawak Research Development Council, 2024)
Introduction: Depression is the most common mental problem (WHO, 2024) and its fast spread is threatening. The number of incidence cases of depression worldwide increased from 172 million in 1990 to 258 million in 2017, comprising an increase of 49.86%. So far the effective treatment of depression remains to be unresolved problem, as at least 30% of people suffer from its treatment resistant form, which is a tremendous individual and social burden. In the pathophysiology of depression, hypothalamic-hypophyseal-adrenal axis (HHAA)is recognize as a major neurobiological link between its inducing factors such as dysfunctional neurogenesis and neurotransmission and immunological and endocrine factor. Experimental research work showed that in modeled stress activation of HHAA results in the development of depression but it remain unknown how depression itself affects HHAA. Nanoparticulate BDNF was shown to be effective in the experimental treatment of neurogenerative diseases, brain trauma and stroke while data regarding nano-BDNF treatment of depression are missing. The objective this study is to assess the effect of nano-BDNF on modelled depression in mice and the underlying and investigate the underlying mechanism of its action on the HHAA. Method: To evaluate the efficiency of Poloxamer 188 and Polysorbate 80 as surfactant for BDNF loading in 100nm PLGA nanoparticulate, an enzyme-linked immunoassay (ELISA) test was performed using different concentration of BDNF. The absorbance of each concentration was measured at 450nm using microplate reader. The obtained data were analyzed using Microsoft excel and one-way ANOVA in IBM SPSS Statistics 26; mean, standard deviation, mean error of Turkey's post hoc test. Shapiro-Wilk test was used for normality of distributions. Thirty six C57BL/6 mice weighing 20-25g were involved in the study. The reserpine model of depression was applied to all animals. Thereafter, mice were divided into 3 groups with 12 per group. Group 1 (negative control) included mice receiving i.v injection of normal saline as a treatment. Group 2 (positive control) involved animals receiving treatment with a standard antidepressant (fluoxetine), group 3 (experimental) was treated with nanoparticulate BDNF with surfactant for seven days. Behavior test were performed at the end of the experiment to assess the severity of depression. They included an open field test (Panlab Harvard with USB digital and smart 3.0 video tracking software, Barcelona, Spain) with the distant walked, rearing, urination and grooming frequencies evaluated and forced swimming test. The corticosterone in blood was measured by ELISA assay by using a microplate reader (SpectraMax iD3, USA). Thereafter the animals were sacrificed by decapitation . Adrenal gland and thymus were sampled for microscopic examination. The histological slaid were stained with hematoxylin-eosin and viewed under the microscope Zeiss Primostar 3 (Jena. Germany). Image analysis were performed using image pro plus 7.0 software (media cybernetics, USA). All results were statistically processed using SPSS 27.0.1 software; one-way ANOVA dispersion analysis was applied with Turkey's test used; for the image analysis of histological slides, Student t-test was applied with p<0.05 indicating of significant of differences.